Main Factors affeting the practice of the English Language out of classrooms among the students of the Bachelor of arts in English Language: Teaching option of the foreign languages Departament of the University of El Salvador - Jereda Mercado, Jaime Ricardo (University of El Salvador, 2005)
In every learning process, practice is an important factor to succeed, especially when referring to language learning. Specialists in teaching the English language agree with the old saying “practice makes perfect”, emphasizing on the importance of the development of the speaking skill among others. However, this does not seem to be taken into account by the students of the Bachelor of Arts (B. A.) in English program of the Foreign Languages Department of the University of El Salvador, who in spite of being majoring in teaching the English language do not practice it out of classrooms due to they are influenced by cultural and personality factors, as well as by the socialization process at the Foreign Languages Department.